Management of LH/FSH deficiency among assisted reproduction specialists in Spain: a Delphi consensus - Lobo, Sonia; Álvaro, Beatriz; Peñarrubia, Joana; García Fernández, Carlos Ignacio; Gil, Elisa; Llácer, Joaquín (Frontiers in Endocrinology, 2025)
BackgroundLuteinizing hormone (LH) and follicle-stimulating hormone (FSH) deficiency can decrease women fertility, due to compromised gametogenesis and steroidogenesis. Several factors, like age, LH/FSH and their receptor polymorphisms, and gonadotrophin-releasing hormone analogue protocols; might result in a hypo-response to ovarian stimulation. The International Committee for Monitoring Assisted Reproduction Technologies (ICMART) highlighted the importance of addressing LH/FSH deficiency for a successful outcome. The aim was to understand if consensus exists on LH/FSH deficiency management among specialists in assisted reproduction based on the latest available evidence.MethodsAn online, two-round Delphi consensus questionnaire was conducted from December 2021 to January 2022. The questionnaire comprised 21 statements concerning the action of LH/FSH in disrupted physiological conditions, clinical presentation of LH/FSH deficiency and its importance in assisted reproduction. A 70% agreement threshold was established for each statement.ResultsResponses from 45 and 42 assisted reproduction Spanish specialists were gathered in the first and second rounds. Consensus was reached in almost half (10/21) of the statements. Participants mostly agreed on the relevance of LH/FSH deficiency due to a reduction of the action and production of gonadotropins, the importance of the effect of different glycosylation variants and age in LH/FSH action and of estradiol (E2) levels during ovulation discharge, the use of POSEIDON criteria to individualize the treatment of patient with poor prognosis, and the use of recombinant LH supplementation in low response patients.ConclusionsIt is important to consider the diverse factors that can lead to LH/FSH deficiency in order to optimize its management and improve reproductive outcomes.